Features of parameters calculation for ntru algorithm - Gorbenko, I. D.; Kachko, O.; Pogrebnyak, K. (ХНУРЭ, 2008)
The paper considers the practical aspects of parameters generation for the NTRU algorithm (ANSI X9.98). The obtained results will allow to generate new sets of parameters to meet the growing requirements for cryptographic security and the availability of new attacks on the lattice.
Keywords: NTRU parameters; cryptographic complexity; error decryption; combined attack